THE FORMATION OF A JAVANESE REFORMED CHRISTIAN SETTLEMENT IN YOGYAKARTA URBAN AREA 1939-1959 - Johny Alfian Khusyairi (Al-Qalam, 2023)
This article examined the connection between primordial and advance features in the formation of Javanese Reformed Christians settlement in urban Yogyakarta. It focused on the causal factors behind the spatial grouping. Most of the Javanese Reformed Christians experienced social mobility which enabled them to have better professions. This research used historical methods by using church archives and various secondary sources. In a way, religion became the ultimate foundation of the formation of spatial grouping for JRC residence in urban Yogyakarta. In another way, the zending fields in urban Yogyakarta did not only facilitate means of social ladder, but also equipped them with careers. This article also found that the formation of urban Protestant settlement in urban Yogyakarta took the same pattern from that of rural areas of Java. Both settlements required relatively distinct territorial unit enclosed as if within foreign territory, so that the residents would easily be focused on Protestant teachings. However, the urban settlement of this Protestant denomination differed in terms of access to modern facilities, such as education, hospital, transportation which proves that the facilities were originally intended for Europeans who mostly were Christians. The Reformed Christian  Javanese benefitted to this facilities because they embraced the same religion as that of the Europeans.